Characterization and Evaluation of Two Novel Fluorescent Sigma-2 Receptor Ligands as Proliferation Probes - Chenbo Zeng; Suwanna Vangveravong; Lynne A. Jones; Krzysztof Hyrc; Katherine C. Chang; Jinbin Xu; Justin M. Rothfuss; Mark P. Goldberg; Richard S. Hotchkiss; Robert H. Mach (Molecular Imaging, 2011)
We synthesized and characterized two novel fluorescent sigma-2 receptor selective ligands, SW120 and SW116, and evaluated these ligands as potential probes for imaging cell proliferation. Both ligands are highly selective for sigma-2 receptors versus sigma-1 receptors. SW120 and SW116 were internalized into MDA-MB-435 cells, and 50% of the maximum fluorescent intensity was reached in 11 and 24 minutes, respectively. In vitro studies showed that 50% of SW120 or SW116 washed out of cells in 1 hour. The internalization of SW120 was reduced ≈30% by phenylarsine oxide, an inhibitor of endocytosis, suggesting that sigma-2 ligands are internalized, in part, by an endocytotic pathway. Subcellular localization studies using confocal and two-photon microscopy showed that SW120 and SW116 partially colocalized with fluorescent markers of mitochondria, endoplasmic reticulum, lysosomes, and the plasma membrane, suggesting that sigma-2 receptors localized to the cytoplasmic organelles and plasma membrane. SW120 did not colocalize with the nuclear dye 4′,6-diamidino-2-phenylindole. In vivo studies showed that the uptake of SW120 in solid tumors and peripheral blood mononuclear cells of mice positively correlated with the expression level of the cell proliferation marker Ki-67, suggesting that sigma-2 fluorescent probes may be used to image cell proliferation in mice.